1990
DOI: 10.1115/1.2920316
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Submicrometer Particles in Dry Sliding Contact

Abstract: The generation of submicrometer-sized particles during dry sliding between stainless steel surfaces is investigated by means of a laser spectrometer for particle counting and scanning tunnelling microscopy for asperity topography characterization. It has been found that, when the submicrometer wear increases with increasing sliding distance or with an initially rougher surface, the number of particles having a submicrometer size is a power function of that size. The two wear coefficients in the power function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is observed that the red-neutral dye was phagocytosed by the macrophages and remained inside the cells indicating that the DLC did not cause disruption of the J774 macrophages cell membrane. From the cytotoxicity studies using a biocompatible glass slides, it is observed that the positive control makes a roseate halo which indicates the cytotoxicity and the negative control did not make any cytotoxicity effect (Xuan et al, 1990) (Figure 3B). Comparing Figure 3A, B, even after 24 hours of contact with films, it is clear that the dye was not released, thereby indicating no cytotoxicity with regard to all samples.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the red-neutral dye was phagocytosed by the macrophages and remained inside the cells indicating that the DLC did not cause disruption of the J774 macrophages cell membrane. From the cytotoxicity studies using a biocompatible glass slides, it is observed that the positive control makes a roseate halo which indicates the cytotoxicity and the negative control did not make any cytotoxicity effect (Xuan et al, 1990) (Figure 3B). Comparing Figure 3A, B, even after 24 hours of contact with films, it is clear that the dye was not released, thereby indicating no cytotoxicity with regard to all samples.…”
Section: Resultsmentioning
confidence: 99%